H3K27Me3 abundance increases fibrogenesis during endothelial-to-mesenchymal transition via the silencing of microRNA-29c - Fledderus, Jolien; Brouwer, Linda; Kuiper, Timara; Harmsen, Martin C.; Krenning, Guido (Frontiers in Cardiovascular Medicine, 2024)
Endothelial-to-mesenchymal transition (EndMT) is a transdifferentiation process in which endothelial cells (ECs) adopt a mesenchymal-like phenotype. Over the past few years, it became clear that EndMT can contribute to several cardiovascular pathologies. However, the molecular pathways underlying the development of EndMT remain incompletely understood. Since the epigenetic enzyme Enhancer of Zeste Homolog 2 (EZH2) and its concomitant mark H3K27Me3 have been shown to be elevated in many cardiovascular diseases that associate with EndMT, we hypothesized that H3K27Me3 is a determinant for the susceptibility of EndMT.To study the association between H3K27Me3 and EndMT, a knockdown model of EZH2 in human endothelial cells (HUVEC) was utilized to reduce H3K27Me3 abundance, followed by induction of EndMT using TGFβ1. The expression of molecular markers of EndMT and fibrogenesis were analysed.In cultured HUVECs, a reduction of H3K27Me3 abundance facilitates EndMT but mitigates fibrogenesis as shown by a decreased expression of collagen I and III. In HUVEC, H3K27Me3 abundance directly affects the expression of miR29c, a collagen-targeting miRNA.Additionally, knockdown of miR-29c in HUVEC with low H3K27Me3 abundance partly restored the expression of collagen I and III. Expectedly, in rats with perivascular fibrosis an increased abundance of H3K27Me3 associated with a decreased expression of miR-29c. In conclusion: our data shows that endothelial fibrogenesis underlies an epigenetic regulatory pathway and we demonstrate that a decreased abundance of H3K27Me3 in ECs blunts fibrogenesis in part in a miR-29c dependent manner. Therefore, a reduction of H3K27Me3 could serve as a novel therapeutical strategy to mitigate fibrogenesis and may prove to be beneficial in fibrogenic diseases including atherosclerosis, cardiac fibrosis, and PAH.